PENINGKATAN MINAT UNTUK MASUK SMPN SATAP 3 TIKEP DENGAN PENINGKATAN KUALITAS PEMBELAJARAN MELALUI PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PENDEKATAN SCIENTIFIC UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA MATERI POKOK GETARAN, GELOMBANG DAN BUNYI - Maalia Maalia (Pascasarjana Universitas Halu Oleo, 2019)
This research was conducted to obtain an overview of students' knowledge in 2 learning cycles. Where the first cycle does not use multimedia as an educational tool. Whereas in the second cycle using multi media as a learning method. Good learning methods can improve student quality and have an impact on school quality. Quality schools can increase the interest and decision of parents to choose a school.The percentage of completeness of science learning outcomes for students of class VIII SMP Satap 3 Tikep on vibration, wave and sound material can be increased by applying the Discovery Learning Model with a Scientific Approach. This is indicated by the value obtained tends to increase from cycle I to cycle II. This is indicated by the acquisition of the average value of learning outcomes in the first cycle of 2.68 with a percentage of 60.61% that have been completed. Whereas in the second cycle the average student learning outcomes increased to 3.01 with a percentage that was completed at 77.78%. Keywords: discovery learning, scientific approach, vibration, waves and sound, consumer interest, consumer decision